Clinical and epidemiological profile of the metabolic syndrome among adults treated at the Hospital I Florencia de Mora EsSalud - Tejada López, Yeny Ofelia (2020)
Objective: To determine the clinical and epidemiological profile of the metabolic syndrome among adults treated at the Hospital I Florencia de Mora EsSalud. Materials and methods: A retrospective, observational and descriptive study conducted in a population of 4,752 patients screened for the Reforma de Vida program. The International Diabetes Federation’s diagnostic criteria for metabolic syndrome were used. Results: The prevalence of metabolic syndrome is 38.97 %. The most frequent variables of the clinical profile were central obesity (97.50 %), low levels of HDL cholesterol (86.4 %) and hypertriglyceridemia (80.10 %). All these variables showed statistical significance. The most frequent variables of the epidemiological profile were female sex (68.10 %) and middleage adult (48.30 %). Conclusions: More than one third of the study population has metabolic syndrome. Obesity, low levels of HDL cholesterol, hypertriglyceridemia, middle-age adult and female sex prevailed in this group.